The United States and Turkey's path to Europe: Hands across the table - (:unkn) unknown (Taylor and Francis, 2015)
Turkey’s relations with the European Union is one of the most enigmatic topics in the European Studies literature. This country, kept at bay by Europeans for centuries, once came unexpectedly close to full-membership. The progress Turkey recorded in its European quest is difficult to account for with either Turkey’s performance or the positive attitude of the Europeans towards Turkey. In this book, Armağan Emre Çakır chronicles over six decades of US involvement in EU-Turkey relations. Shedding new light on the reasons, characteristics, transformation and relative importance of the US influence on Turkey-EU relations, he argues that Turkey’s quest for EU membership would not have advanced this far without the support from the United States. Çakır’s hypotheses and findings are grounded in original research that, among other things, includes interviews conducted on both sides of the Atlantic with key players, archival material and newspaper articles. The valuable insights presented in this book make for a much needed alternative history of this volatile relationship. © 2016 Taylor and Francis.